2022
DOI: 10.22271/micro.2022.v3.i2a.47
|View full text |Cite
|
Sign up to set email alerts
|

Proteus bacteria species from hospital sewage and Mfoundi River in Yaounde (Cameroon, Central Africa): Comparison of the diversity, abundance and susceptibility against some β-lactams, Quinolones and Aminoglycosides antibiotics

Abstract: Species of the genus Proteus are the cause of several infections and represent one of the microorganisms commonly involved in hospital infections. These infections are sometime difficult to treat because the antibiotic resistance phenomenon, which represents one of the greatest health challenges today. This study aimed at comparing the diversity, abundance and antimicrobial susceptibility of Proteus species isolated from hospital wastewater and Mfoundi River in Yaounde (Cameroon, Central Africa). The physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Antimicrobial resistance can be intrinsic or acquired. In the latter case, resistance can arise from mutation of bacterial DNA or from the acquisition of resistance genes by means of horizontal gene transfer, with DNA passing from one bacteria to another [23][24][25]. It is also indicated that the release of hospital wastewater in the natural environment is a source of both antibiotics and antibiotic resistance genes in groundwater, based on their spatial spreading [26].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance can be intrinsic or acquired. In the latter case, resistance can arise from mutation of bacterial DNA or from the acquisition of resistance genes by means of horizontal gene transfer, with DNA passing from one bacteria to another [23][24][25]. It is also indicated that the release of hospital wastewater in the natural environment is a source of both antibiotics and antibiotic resistance genes in groundwater, based on their spatial spreading [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the people who use these waters for their food because of their apparent clarity are unaware of their microbiological quality [6]. To this end, the authorities now need to take a particular interest in monitoring waterborne diseases, by developing new approaches that link the control of serious diseases caused by disinfection byproducts to the control of the most resistant micro-organisms [7]. In Cameroon, several studies have already been carried out on water quality in the town of Ntui.…”
Section: Introductionmentioning
confidence: 99%